Comparative analysis of methods estimating the population of Ukraine - Pasichnyk, A. N.; Medvediev, I. P.; Pasichnyk, A. V. (Systems and Technologies, 2020)
The methodical approach of construction of an estimation of population of Ukraine on the basis of the systematic analysis of statistical data of natural and migratory movement of the population, labor potential of the country is offered. Estimates of the current population of Ukraine were constructed on the basis of the proposed approaches and a comparative analysis of the obtained results was conducted and their discrepancy was determined. The relationship of the obtained results with the calculated data of a comprehensive population assessment carried out by the Cabinet of Ministers of Ukraine in 2019 is also considered. It is shown that Ukraine can become a successful country only if it provides favorable socio-economic conditions for sustainable growth of labor capital based on population growth, rejuvenation of its age structure, job creation through development and introduction of innovative technologies. It is established that one of the main tasks of public administration is to conduct an effective national demographic policy aimed at reproducing the quantitative and qualitative composition of the population of Ukraine. In recent decades, there has been a clear trend of population decline in Ukraine due to lower birth rates and increased mortality, as well as due to mass trips of Ukrainian citizens abroad in search of work. The demographic situation in the country is complicated by both the economic crisis and global competition from developed countries for labor resources. Given the importance of solving demographic problems for national security, the results of the study show that Ukraine needs to use the experience of highly developed countries and persistently pursue public policies aimed at creating favorable conditions for attracting young people for both education and employment. Therefore, the development and implementation of effective management decisions to solve the demographic problems of Ukraine and solve problems in various spheres of government and business should be based on current data on the population of the country. This involves further development and improvement of the proposed approaches aimed at increasing heir accuracy and reliability.